2000
DOI: 10.1177/109467050024005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Incomplete Information on the Use of Marketing Research Intelligence in International Service Settings

Abstract: Unfamiliarity with foreign business environments and cultures will result in higher levels of uncertainty, especially for international service organizations. To effectively deal with international uncertainty, it seems crucial to have access to information that is as complete as possible. In practice, however, information is hardly ever complete. To date, little is known about the impact of incomplete information on the decision-making processes in international service firms. This article examines the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
1
10
0
2
Order By: Relevance
“…These beliefs occur through inferential processes (Van Birgelen et al 2000), through an elaboration of meaning beyond that provided explicitly (Pinson 1986). Thus inferential beliefs are due to halo effects (Broniarczyk and Alba 1994) based on strong mental inter-attribute associations (Johnson and Levin 1985;Kardes 1988).…”
Section: Organic Labels As Signals Of Product Qualitymentioning
confidence: 99%
“…These beliefs occur through inferential processes (Van Birgelen et al 2000), through an elaboration of meaning beyond that provided explicitly (Pinson 1986). Thus inferential beliefs are due to halo effects (Broniarczyk and Alba 1994) based on strong mental inter-attribute associations (Johnson and Levin 1985;Kardes 1988).…”
Section: Organic Labels As Signals Of Product Qualitymentioning
confidence: 99%
“…This is a plausible explanation, as the absence of specific cues allows the viewers to complement the missing information with their own relevant information (Chebat et al, 2001(Chebat et al, , 2003a. Hence, available visual information in the present experimental ad may have enabled experienced consumers to act on the basis of limited amounts of information (Birgelen et al, 2000). Overall, the results suggest that the high level of cognitive activity triggered by involvement results in inference making for service quality (Chebat et al, 2003a).…”
Section: Discussionmentioning
confidence: 79%
“…This finding is similar to that of Yates and colleagues (1978) who found that attitude ratings for the partially described profiles tended to be low. Analogously, Birgelen, Ruyter, and Wetzels (2000) found that incomplete information leads to less positive attitudinal and behavioral evaluative judgments compared to when information is complete. Considering the effort needed to compensate for incomplete information (e.g., external search), missing information may diminish liking of the ad, which in turn may affect consumers' attitudes toward the advertised product.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…581-604 www.jistem.fea.usp.br 586 information about the values of each alternative across multiple dimensions (Payne, Bettman & Johnson, 1993). Birgelen, Ruyter & Wetzels (2000) state that missing information is unlikely to be ignored or denied by decision makers; and several studies have shown that decision makers tend to reasoning based on the assumption and extrapolation or will predict the missing information of other available information. Table 2 shows the summary of studies on Missing Information in decision making, with the main research contributions on this topic, as well as the theme and context in which they were conducted:…”
Section: Influence Of Missing Information In Decision Makingmentioning
confidence: 99%